Histological analysis after arm tip amputation in the brittle star Ophioplocus januarii (Echinodermata: Ophiuroidea) - Di Giorgio, Gisele Vanesa (2015)
Arm tip regeneration after amputation in the brittle star Ophioplocus januarii was examined in order to observe the histological and morphological changes leading to arm regeneration. The process of regeneration is described and compared with other brittle stars species. The regenerative process of arm regeneration in O. januarii involves the closure of the wound, the repair of the tissue damage and posterior formation of a presumptive stalked blastema by undifferentiated cells, sclerocytes and presumptive blastemic cells. The sclerocytes are the more abundant cell type during the regeneration process. This evidence confirms the regenerative process described in other brittle stars species and suggests this process is a common feature among the Ophiuroidea.